Application of the Stockwell Transform to Electroencephalographic Signal Analysis during Gait Cycle - Ortiz, Mario; Rodríguez-Ugarte, Marisol; Iáñez, Eduardo; Azorín, José M. (Frontiers in Neuroscience, 2017)
The analysis of electroencephalographic signals in frequency is usually not performed by transforms that can extract the instantaneous characteristics of the signal. However, the non-steady state nature of these low voltage electrical signals makes them suitable for this kind of analysis. In this paper a novel tool based on Stockwell transform is tested, and compared with techniques such as Hilbert-Huang transform and Fast Fourier Transform, for several healthy individuals and patients that suffer from lower limb disability. Methods are compared with the Weighted Discriminator, a recently developed comparison index. The tool developed can improve the rehabilitation process associated with lower limb exoskeletons with the help of a Brain-Machine Interface.